Extracellular potassium effects are conserved within the rat erg K(+) channel family - Sturm, Patrick (Blackwell Science Inc, 2005)
The biophysical properties of native cardiac erg1 and recombinant HERG1 channels have been shown to be influenced by the extracellular K(+) concentration ([K(+)](o)). The erg1 conductance, for example, increases dramatically with a rise in [K(+)](o). In the brain, where local [K(+)](o) can change considerably with the extent of physiological and pathophysiological neuronal activity, all three erg channel subunits are expressed. We have now investigated and compared the effects of an increase in [K(+)](o) from 2 to 10 mm on the three rat erg channels heterologously expressed in CHO cells. Upon increasing [K(+)](o), the voltage dependence of activation was shifted to more negative potentials for erg1 (ΔV(0.5) =−4.0 ± 1.1 mV, n = 28) and erg3 (ΔV(0.5) =−8.4 ± 1.2 mV, n = 25), and was almost unchanged for erg2 (ΔV(0.5) =−2.0 ± 1.3 mV, n = 6). For all three erg channels, activation kinetics were independent of [K(+)](o), but the slowing of inactivation by increased [K(+)](o) was even more pronounced for erg2 and erg3 than for erg1. In addition, with increased [K(+)](o), all three erg channels exhibited significantly slower time courses of recovery from inactivation and of deactivation. Whole-cell erg-mediated conductance was determined at the end of 4 s depolarizing pulses as well as with 1 s voltage ramps starting from the fully activated state. The rise in [K(+)](o) resulted in increased conductance values for all three erg channels which were more pronounced for erg2 (factor 3–4) than for erg1 (factor 2.5–3) and erg3 (factor 2–2.5). The data demonstrate that most [K(+)](o)-dependent changes in the biophysical properties are well conserved within the erg K(+) channel family, despite gradual differences in the magnitude of the effects.